Infantile Bullous Pemphigoid Treated Using Intravenous Immunoglobulin: Case Report and Review of the Literature - YÜCELTEN, AYŞE DENİZ (WILEY-BLACKWELL, 2015)
We report a 5-month-old girl diagnosed with bullous pemphigoid who initially did not respond to systemic corticosteroids and dapsone but rapidly improved after the addition of intravenous immunoglobulin (IVIG) infusions. A literature search revealed anecdotal cases of infantile bullous pemphigoid treated with IVIG, although variable treatment regimens were used, and some resistant cases required additional medications such as rituximab for clinical remission.
Keywords: RITUXIMAB; INFANCY